Feminist Global Political Economy and Feminist Security Studies? The Politics of Delineating Subfields. Issue 4 (24th November 2017) - Stern, Maria
Abstract : When considering possible conversations, synergies, overlaps, similarities, conflicts, and distinctions between two subfields or "camps" (Sylvester 2010), the question of limits looms large. Where, why, and how are the limits of feminist security studies (FSS) and feminist global political economy (FGPE) currently being drawn, and to what effect? Building upon previous conversations about the relationship between FSS and FGPE, particularly as they were discussed in the Critical Perspectives section in Politics & Gender (June 2015), as well as those about FSS and FGPE more generally, I briefly touch on a few central points regarding the politics of boundary drawing and the practices of feminist research.